2007
DOI: 10.1177/1077801207301557
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bullying and Sexual Harassment on Middle and High School Girls

Abstract: The impact of bullying and sexual harassment on six health outcomes among middle school girls were compared to these outcomes among high school girls. High school girls experienced more bullying and sexual harassment and poorer health outcomes than their middle school counterparts, but the impact of these experiences was less among high school students. Differences in outcomes may be the result of better support systems and coping mechanisms among high school girls and/or challenging developmental changes duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 23 publications
(34 reference statements)
12
109
1
5
Order By: Relevance
“…Specifically, bullying perpetration early in middle school predicted sexual harassment perpetration 3 years later. An increase in sexually harassing behavior between middle school and high school was also found in a study of girls (Gruber & Fineran, 2007). In contrast to bullying, sexual harassment involves greater cross-sex behavior where girls are the primary targets of boys.…”
Section: Who Are the Targets Of Bullying And Sexual Harassment?mentioning
confidence: 72%
“…Specifically, bullying perpetration early in middle school predicted sexual harassment perpetration 3 years later. An increase in sexually harassing behavior between middle school and high school was also found in a study of girls (Gruber & Fineran, 2007). In contrast to bullying, sexual harassment involves greater cross-sex behavior where girls are the primary targets of boys.…”
Section: Who Are the Targets Of Bullying And Sexual Harassment?mentioning
confidence: 72%
“…American studies adolescent students showed that those victims of frequent episodes of sexual harassment or threat during their school years presented outcomes associated with relationship problems and hyperactivity (82) .…”
Section: Std/aids Relatedmentioning
confidence: 99%
“…Furthermore, strained peer and parental relations are associated with elevated levels of psychological distress [12]. Bullying has been investigated as a determinant of psychological distress [13,14], although sexual harassment has not been addressed to the same degree. However, examples of studies of sexual harassment show that being a target of sexual harassment is common and has an impact on well being and psychological distress in adolescents [14][15][16].…”
Section: Introductionmentioning
confidence: 99%